STUDI KASUS RUPTURE PERINEUM PADA IBU BERSALIN DI PMB MASFUFAH - Lia Windi Inara; Hayun Manudyaning Susilo; Fetty Rosyadia Wachdin; Nur Hidayati (Universitas Muhammadiyah Ponorogo, 2022)
Perineal rupture is an injury to the birth canal that occurs spontaneously which can occur from various complications, one of which is during the second stage of labor so that it can cause loss of normal function in the reproductive organs in women such as a stiff perineum. As a result of the pelvic floor muscles that are often tense is one of the causes of perineal tears, especially in primigravida. The results of the implementation of midwifery care aims to determine the factors that relate to the occurrence in the second stage of maternity mothers. The method used is the midwifery management approach with the SOAP method, through a qualitative descriptive type of research with a case study approach to midwifery care conducted at PMB Masfufah Badegan Ponorogoon Mrs. A 22 years old. Childbirth in the second stage with rigid perineal problems. After the mother was given some care and guidance, the perineal problem remained tense due to the mother's fear, so she was forced to cut the episiotomy so as not to hinder the continuation of labor.